Knowledge Sharing and Individual Diversity Interaction at Zakat Institutions in Indonesia: Testing the Relationship - Kuntarno Noor Aflah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Research on the relationship between knowledge sharing and employee performance is still inconsistent. Hence, this study offers novelty by involving a variable of individual diversity interaction to investigate the effect of knowledge sharing on employee performance as observed by the ability of employees in achieving individual targets in collecting and distributing ZIS (zakat, infak, and alms). This study included 195 respondents that were analyzed with Structural Equation Modelling using AMOS. The results indicated that knowledge sharing has a positive and significant effect on individual diversity interaction. Individual diversity interactions have a positive and significant effect on religiosity and affective commitment. Moreover, religiosity and individual diversity interaction have a positive and significant effect on employee performance. However, affective commitment indicates no effect on employee performance. This study suggests that to improve performance, employees at zakat institutions need to further intensify their knowledge sharing. This study can be utilized as a resource for more research and to upgrade employees' ZIS collection and distribution capacity.